Structural associations between organelle membranes in nectary parenchyma cells - Machado, Silvia Rodrigues [UNESP]; Gregório, Elisa A. [UNESP]; Rodrigues, Tatiane M. [UNESP] (Springer Nature, 2018)
Main conclusion: The close association between membranes and organelles, and the intense chloroplast remodeling in parenchyma cells of extrafloral nectaries occurred only at the secretion time and suggest a relationship with the nectar secretion. Associations between membranes and organelles have been well documented in different tissues and cells of plants, but poorly explored in secretory cells. Here, we described the close physical juxtaposition between membranes and organelles, mainly with chloroplasts, in parenchyma cells of Citharexylum myrianthum (Verbenaeceae) extrafloral nectaries under transmission electron microscopy, using conventional and microwave fixation. At the time of nectar secretion, nectary parenchyma cells exhibit a multitude of different organelle and membrane associations as mitochondria–mitochondria, mitochondria–endoplasmic reticulum, mitochondria–chloroplast, chloroplast–nuclear envelope, mitochondria–nuclear envelope, chloroplast–plasmalemma, chloroplast–chloroplast, chloroplast–tonoplast, chloroplast–peroxisome, and mitochondria–peroxisome. These associations were visualized as amorphous electron-dense material, a network of dense fibrillar material and/or dense bridges. Chloroplasts exhibited protrusions variable in shape and extension, which bring them closer to each other and to plasmalemma, tonoplast, and nuclear envelope. Parenchyma cells in the pre- and post-secretory stages did not exhibit any association or juxtaposition of membranes and organelles, and chloroplast protrusions were absent. Chloroplasts had peripheral reticulum that was more developed in the secretory stage. We propose that such subcellular phenomena during the time of nectar secretion optimize the movement of signaling molecules and the exchange of metabolites. Our results open new avenues on the potential mechanisms of organelle contact in parenchyma nectary cells, and reveal new attributes of the secretory cells on the subcellular level.
Keywords: Chloroplast remodeling; Membrane association; Nectary; Organelle juxtaposition; Plastidial protrusions